Between Social Tutelage and Individual Responsibility: Dilemmas of Higher Education in Eastern Europe. (April 2014) - Peshkopia, Ridvan
What explains the crisis of the Eastern European universities, and how can they overcome it? This article tries to find the causes of such a crisis in the communist tradition and the lingering communitarian systems of thought in Eastern Europe. The current state-controlled academic systems in the region continue to reproduce such a culture. Instead, this article suggests the transformation of Eastern European universities to entrepreneurial universities focused on creating entrepreneurial graduates who invest in and benefit from their careers. A university—industry—government triple helix model would have been the right model had not industry in many Eastern European countries collapsed under communist regimes. In such a case, universities should take over the task of encouraging industry creation. Also, other societal stakeholders might help.